2017
DOI: 10.1111/1440-1681.12799
|View full text |Cite
|
Sign up to set email alerts
|

A co‐drug conjugate of naringenin and lipoic acid mediates neuroprotection in a rat model of oxidative stress

Abstract: Using our in vitro and in vivo models of oxidative stress, the current study was designed to determine the neuroprotective potential of naringenin, alone or in combination with lipoic acid. In our mixed neuronal culture exposed to hypoxia and subsequent reoxygenation, naringenin was shown to provide significant neuroprotection against cell death at a concentration of 2.5 μmol/L. Lipoic acid (LA) did not produce neuroprotection at any concentration tested (0.25-100 μmol/L). In contrast, when naringenin was cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In an in vivo model of ischemia-reperfusion injury following transient occlusion of the middle cerebral artery (tMCAO), pre-administration of either naringenin or conjugated formulation significantly abrogated infarct size. The potency of the novel formulation was 10,000-fold compared to naringenin alone [156].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In an in vivo model of ischemia-reperfusion injury following transient occlusion of the middle cerebral artery (tMCAO), pre-administration of either naringenin or conjugated formulation significantly abrogated infarct size. The potency of the novel formulation was 10,000-fold compared to naringenin alone [156].…”
Section: Naringenin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…It is also known as grapefruit flavonoid naringenin. It has been demonstrated that flavonoid naringenin has anti-inflammatory, antioxidant and neuroprotective properties (17,18). Surprisingly, it has been reported that citrus juices such as grapefruit juice interfere with the metabolism of the opiates and maximizes their effects (19).…”
Section: Introductionmentioning
confidence: 99%
“…As inflammatory damage is implicated in the etiology of ischemia/reperfusion (I/R) induced complications, flooding the system with anti-inflammatory herbs may be a sensible step. , Naringenin, a flavonoid is being vigorously investigated as a possible candidate to protect against ischemic stroke and other related CNS disorders. Naringenin is a natural compound that possesses various effects like antioxidants and anti-inflammatory with a known suppressant activity against NF-kβ activation. Thus, it has a promising therapeutic potential against ischemic reperfusion activated NF-kβ pathway. However, the low water solubility and, thus, the poor oral bioavailability (5.81%) remain a big challenge in the clinical development of naringenin. , …”
Section: Introductionmentioning
confidence: 99%